2014
DOI: 10.1027/1618-3169/a000227
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Adjustment to Conflict Strength

Abstract: Current models of cognitive control assume gradual adjustment of processing selectivity to the strength of conflict evoked by distractor stimuli. Using a flanker task, we varied conflict strength by manipulating target and distractor onset. Replicating previous findings, flanker interference effects were larger on trials associated with advance presentation of the flankers compared to simultaneous presentation. Controlling for stimulus and response sequence effects by excluding trials with feature repetitions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 60 publications
4
26
1
Order By: Relevance
“…It is unclear, however, why the CSE was completely absent in simultaneous trials, wherein a sizable congruency effect was also observed. The conflict monitoring hypothesis posits that experienced response conflict in the previous trial, as indexed by the size of the congruency effect, drives the CSE (Botvinick et al, 2001;Wendt et al, 2014;Yeung, Cohen, & Botvinick, 2011). Thus, this hypothesis is able to explain why the CSE was larger when the previous trial involved sequential as compared to simultaneous presentation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is unclear, however, why the CSE was completely absent in simultaneous trials, wherein a sizable congruency effect was also observed. The conflict monitoring hypothesis posits that experienced response conflict in the previous trial, as indexed by the size of the congruency effect, drives the CSE (Botvinick et al, 2001;Wendt et al, 2014;Yeung, Cohen, & Botvinick, 2011). Thus, this hypothesis is able to explain why the CSE was larger when the previous trial involved sequential as compared to simultaneous presentation.…”
Section: Discussionmentioning
confidence: 93%
“…whether it is maximal when the distracter appears shortly before the target or simultaneously with the target (Appelbaum, Boehler, Won, Davis, & Woldorff, 2012;Donohue, Appelbaum, Park, Roberts, & Woldorff, 2013;Glaser & Glaser, 1982;Mattler, 2003;Wendt, Kiesel, Geringswald, Purmann, & Fischer, 2014). Although investigating the sources of this variability was not the aim of our study, we made use of it when considering whether certain variants of the attentional shift account, which posit a strong relationship between the CSE and the congruency effect, could explain our findings.…”
Section: The Present Studymentioning
confidence: 84%
“…At least one cognitive control account-the conflict monitoring model-appears to posit that the size of the CSE should vary positively with the size of the congruency effect (Botvinick et al, 2001;Wendt, Kiesel, Geringswald, Purmann, & Fischer, 2014;Yeung, Cohen, & Botvinick, 2011). To investigate this possibility, we determined whether the congruency effect in the mean RT data was larger in the Simon task, which exhibited a relatively large CSE, than in the Stroop and Flanker tasks, which exhibited rela tively small CSEs.…”
Section: Across-task Analysesmentioning
confidence: 96%
“…Questions of interest concerned the locus and specificity of the adaptation effect (e.g., Kiesel et al, 2006; Kunde and Wühr, 2006; Notebaert and Verguts, 2008; Wendt et al, 2012), the role of episodic retrieval and priming processes (e.g., Mayr et al, 2003; Hommel et al, 2004), the role of learning (e.g., Holroyd and Coles, 2002; Blais et al, 2007; Verguts and Notebaert, 2009; Blais and Verguts, 2012), timing (e.g., Goschke and Dreisbach, 2008; Scherbaum et al, 2011; Pastötter et al, 2013), conflict strength (e.g., Takezawa and Miyatani, 2005; Forster et al, 2011; Wendt et al, 2014), working memory load (Stürmer et al, 2005; Fischer et al, 2010; Soutschek et al, 2012), and context effects in general (e.g., Fischer et al, 2008; Funes et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…For example, presenting Stroop conflict stimuli (Stroop, 1935) as primes eased the evaluation of negative target stimuli and increased the frequency of negative judgments for neutral target stimuli (Dreisbach and Fischer, 2012b; Fritz and Dreisbach, 2013, 2014). Converging evidence in favor of the aversive conflict signal also comes from physiological studies showing increased heart rate (Renaud and Blondin, 1997), larger pupil dilatation (van Steenbergen and Band, 2013; Wendt et al, 2014), and enhanced skin conductance response (Kobayashi et al, 2007) in response to incongruent Stroop stimuli (but see Schacht et al, 2010, who, however, did not use Stroop stimuli but measured physiological activity during a go/no-go paradigm). Given that conflicts are detected by the ACC, and further given that the ACC is also activated by monetary loss (Rainville, 2002), social exclusion (Eisenberger et al, 2003), negative feedback (Nieuwenhuis et al, 2004), and pain (Singer et al, 2004), one might therefore speculate that it is not the response conflict per se but the aversive character of the response conflict that triggers the processing adjustments (Botvinick, 2007; Dreisbach and Fischer, in press a, in press b).…”
Section: Introductionmentioning
confidence: 99%